Learning interreligiously: in the text, in the world - Clooney, Francis X. (Fortress Press, 2018)
Learning Interreligiously offers a series of about one hundred short pieces, written online between 2008 and 2016. They are meant for a wide range of readers interested in interreligious dialogue, interreligious learning, and the realities of encounters between Hinduism and Christianity, and are rich in insights drawn from teaching, travels in America and India, and the author’s research on sacred texts. The author, a Catholic priest who has spent more than forty years learning from Hinduism and observing religion as a plus and minus in today’s world, has much to share with readers. Some pieces were prompted by items in the news, some go deeper into traditions and probe the rich Scriptures and practices going back millennia, some seek simply to provoke fresh thinking, and others invite spiritual reflection. The book is divided into several parts so that readers can focus on individual events that made the news or on longer term and more concerted study. Familiar texts such as the Yoga Sutras, the Bhagavad Gita, the Qur’an, and key passages from the New Testament will be considered for their spiritual possibilities. Readers will find much here to learn from and respond to as they too consider religion in today’s world. -- From back cover